Understanding perspectives of HIV/AIDS affected households on food and nutrition interventions and social protection programmes in Zimbabwe - George, Kembo; Dembedza, Mavis Precious; Lesley, Macheka (Frontiers in Nutrition, 2024)
The study was aimed at understanding the needs and perspectives of HIV affected households on food and nutrition security intervention programmes. The study used qualitative methods that include focus groups discussions and key informant interviews to solicit for lived experiences of People Living With HIV (PLWHIV). The results revealed that intervention programmes by both government and development partners (donors) can be divided into four (4) categories: food and nutrition security, livelihood, health, and social protection. Interventions that targeted health included the provision of HIV antiretroviral drugs to PLWHIV and counselling to both PLWHIV and affected persons. Intervention programmes targeted at social protection included provision of food aid and cash transfers. The recommendations based on the research findings are that intervention programmes should focus more on resilience building as a way of building capacity of PLWHIV. This way, sustainability of intervention programmes is improved. As such, it is important to ensure, through policy, that all intervention programmes have a component of capacity building to improve resilience of participants and programme sustainability. Furthermore, there is a need to improve targeting for beneficiaries of intervention programmes and clearly define the "vulnerable" group.